PubChem in 2021: new data content and improved web interfaces. Issue Volume 49:Issue D1(2021) (5th November 2020) - Kim, Sunghwan; Chen, Jie; Cheng, Tiejun; Gindulyte, Asta; He, Jia; He, Siqian; Li, Qingliang; Shoemaker, Benjamin A; Thiessen, Paul A; Yu, Bo; Zaslavsky, Leonid; Zhang, Jian; et al.
Abstract: PubChem (https://pubchem.ncbi.nlm.nih.gov ) is a popular chemical information resource that serves the scientific community as well as the general public, with millions of unique users per month. In the past two years, PubChem made substantial improvements. Data from more than 100 new data sources were added to PubChem, including chemical-literature links from Thieme Chemistry, chemical and physical property links from SpringerMaterials, and patent links from the World Intellectual Properties Organization (WIPO). PubChem's homepage and individual record pages were updated to help users find desired information faster. This update involved a data model change for the data objects used by these pages as well as by programmatic users. Several new services were introduced, including the PubChem Periodic Table and Element pages, Pathway pages, and Knowledge panels. Additionally, in response to the coronavirus disease 2019 (COVID-19) outbreak, PubChem created a special data collection that contains PubChem data related to COVID-19 and the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).